Berkelanjutan, kesejakterahan, p Optimizing Sustainable Agricultural Practices in Improving the Welfare of Coffee Farmers: Case Study in Banyuwangi Regency: Optimalisasi Praktik Pertanian Berkelanjutan dalam Meningkatkan Kesejahteraan Petani Kopi: Studi Kasus di Kabupaten Banyuwangi - Sugiharto, Firsta Bagus; Rizal Dhofir; Abdul Hamid; Tomas Surandoko (LPPM UNINUS, 2024)
Sustainable agriculture is an important approach to improving the welfare of farmers in Indonesia, requiring understanding and application of sustainable technologies by many farmers. The community service program titled